The Principal's Strategy in Developing the Scout and Flag Raising Team Programs at Darunnajah Islamic Boarding School - Rokimin; Dudun Ubaedullah (At-Tathbīq: Journal of Education and Learning, 2025)
ABSTRACT This study aims to analyze the development of the Pramuka (Scouting) and Paskibra (Flag Hoisting Troop) programs at Pondok Pesantren Darunnajah through the lens of three key management functions: planning, organizing, and controlling. These functions are considered foundational pillars in managing character and leadership education programs within the Islamic boarding school environment. The research employed a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation of extracurricular activities conducted in the pesantren. The findings reveal that the planning function was implemented systematically, with clearly defined objectives and participatory forums such as the Musyawarah Dewan Ambalan for designing annual work plans. The organizing function was reflected in a well-structured organizational hierarchy, clear division of roles and responsibilities, and the strategic assignment of qualified mentors and trainers. The controlling function combined direct supervision through regular on-site inspections and indirect supervision through accountability reports and annual evaluation forums. Additionally, student participation in the Pramuka program was integrated into the national education data system (Dapodik), reinforcing accountability and motivation. The implications of this study suggest that consistent application of management functions significantly enhances the effectiveness of extracurricular programs in shaping students' character and leadership. This model of educational program management can serve as a reference for other Islamic educational institutions seeking to implement structured, sustainable, and character-oriented extracurricular initiatives.